Health Care for NFL Players: Upholding Physician Standards and Enhancing the Doctor-Patient Relationship - Duvernay-Tardif, Laurent (The Hastings Center report, 2016)
Beginning my third year with the Kansas City Chiefs and being also a medical student at McGill University, I was at first a little reluctant to comment on Glenn Cohen et al.’s critique of the National Football League's structure involving player health and team doctors, but the opportunity to provide a perspective as both a football player and a medical student was too much to forgo. Because of my athletic and academic background, I am often asked what I think about injuries in professional sports and about the role of sports medicine physicians, and Cohen et al.’s article demands a thoughtful reaction. I want to suggest that the fundamental principles concerning the medical profession and the doctor-patient relationship provide additional arguments for some of the solutions that Cohen et al. discuss. The professional self-regulation that the proposed medical committee could provide and the reliance on a doctor who was not hired by the player's employer—the club—for a second opinion are both good ways to minimize conflicts of interest.